Peran Regulasi Keuangan Berkelanjutan terhadap Tingkat Kesiapan Wajib Pajak dalam Penerapan Pajak Karbon di Indonesia - Andrew Christian Sudjono; Amelia Setiawan (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The carbon tax regulation that will be implemented in Indonesia has been postponed considering the macroeconomic situation that is happening nowadays. This research studies the readiness for its implementation in Indonesia by assessing the implementation of POJK No. 51 in 2021 which regulates the carbon emission disclosure in the sustainability report. In addition, this research discusses an effective scheme for carbon tax implementation in Indonesia based on POJK No. 51. The data that is used in this research mainly is secondary data obtained from coal sector companies’ sustainability reports in Indonesia which are listed in Bursa Efek Indonesia for 2021, government’s regulation, and previous studies about the carbon tax. It is found that 34,62% of the coal companies haven’t disclosed their carbon emission. However, POJK No. 51 is proven to improve the readiness of the coal sector companies for the tax carbon implementation. Carbon tax implementation can use sustainability report that published by each company, which already contains the carbon emission. Even though, a more detailed regulation is still needed to support the carbon tax implementation based on the carbon emission disclosure by coal companies in 2021.